COMPETITIVENESS ANALYSIS AND STRATEGY FORMULATION IN IMPROVING INDONESIAN COFFEE COMMODITIES - Ujang Maman; Achmad Tjachja Nugraha; Setiadi Amarullah (AGRIBUSINESS JOURNAL, 2021)
This research was motivated by a decline in Indonesia's export rating due to several problems such as limited capital and technology, a decrease in plantation area, the amount of coffee production, and the productivity of coffee plants, as well as the low quality of coffee produced had an impact on international trade in Indonesian coffee.  This study aims to 1) analyze the condition of coffee agribusiness in Indonesia, 2) analyze the competitiveness of Indonesian coffee both comparatively and competitively, and 3) analyze and formulate the right strategy to improve the competitiveness of Indonesian coffee. The data used is secondary data from 2015-2019.The results of the descriptive analysis showed that the marketing subsystem found that the coffee business chain in Indonesia has not been effective because the marketing flow at the farmer level is still long and causes large price margins. On the other hand, financial institutions as support have also not supported coffee agribusiness activities, especially in providing financing support to farmers. Based on the results of the comparative competitiveness analysis of Indonesian coffee in the international market using the RCA method, it produces an average value of 5.76 which shows that Indonesia has comparative competitiveness. However, when compared to the average RCA value of other coffee exporter countries, Indonesia is the lowest. This shows that Indonesia is still less competitive. Based on the analysis using the Porter Diamond System, shows that Indonesian coffee has competitiveness competitively because four of the six main pairs of components have mutually supportive links. Based on the SWOT matrix, the focus of the S–O strategy (using the main force to seize the opportunities at hand) obtained five strategies to increase competitiveness.